Health Perception and Management of Household Members of Patients with Pulmonary Tuberculosis - Edmelyn B. Cacayan; Jewelle C. Sevilla; Michelle D. Chy (Health Notions, 2020)
Reducing and controlling incident rate of Pulmonary Tuberculosis was the goal of the Department of Health thus coming up with a program called Direct Observed Treatment Short-course (DOTS).This study would like to know the health perception and management of household members on patient with pulmonary tuberculosis. The participant involved in this study are the household members of patient diagnosed with pulmonary tuberculosis from the month of January to March with highest rate with in the poblacion barangays of Echague Isabela. The researcher used a survey questionnaire and was given to 30 household members of patients with Pulmonary Tuberculosis wherein they have evaluated their health Perception and Management on Pulmonary Tuberculosis. The Health Perception and management of household members were acquired using the likert scale that was created by the researcher wherein the highest is 5 which is equivalent to ALWAYS and 1 or NEVER was the lowest. The researcher used a equivalent to ALWAYS and 1 or NEVER was the lowest. The researcher used a descriptive survey design to collect information from the respondents. The researcher used SPSS for the tabulation and determining the frequency and percentage, t-value and f-value is used to determine the difference of respondents profile and Pearson's r- correlation is used to determine the relationship between the health perception and health management. Results revealed that the Health Perception of the Respondent shown that they are in average knowledge about TB. The health management of the respondents shown that they are knowledgeable but not enough. Keywords: health perception; health management; pulmonary tuberculosis